A Profile of the Upper Middle Class Compulsive Buyer in Mexico City - Mondragón, Carlos; Merino, Maria (Cuadernos de Estudios Empresariales, 2013)
This study focuses on examining the behavior of compulsive shoppers, women of the upper middle class in Mexico City, with the intention of creating a profile of women shoppers with the characteristics of compulsive buyers. As the objective of the study is the definition of a segment of Mexican women with greater compulsion to buy, it was decided that a conglomerate analysis would be applied in order to classify individuals in relatively similar groups, in terms of the considered variables. The compulsive shopper experiences anxiety or depression as a result of the expenses incurred when buying; nonetheless, neither the anxiety nor the depression can be attributed to just the act of buying, but rather that has these feelings form an important part of the compulsive individual’s own behavioral, cognitive, or physiological symptoms. The recurring impulse of the compulsive shopper however, causes the behavior to be repeated again and again as an attempt to reduce this distress, which never occurs. This study will focus on four aspects shown by the shoppers: 1) materialism, 2) negative emotions associated with consumption, 3) impulsiveness of consumption, and 4) positive emotions associated with consumption. The empirical validity of the consumer profile will be examined.